Determinant analysis of infant’s basic immunization visits during the covid-19 pandemic - Rionitara Wikarya; Roza Sriyanti; Rinang Mariko (Institute of Computer Science (IOCS), 2023)
The COVID-19 pandemic had an impact on the implementation of health programs, especially immunization services. This is certainly a risk for the occurrence of PD3I Extraordinary Events. The coverage of basic immunization in Padang City was so far from the national basic immunization target that has been set were 95%, coverage of BCG immunization (74.6%), DPT-HB-HIB immunization (55.5%), polio immunization (49%) and MR immunization (46%). Health behavior, especially basic immunization, can be influenced by several determinants. This study aims to determine the determinants of basic immunization visits for infants during the COVID-19 pandemic in the West Rawang Health Center, Padang City working area. This research was a quantitative approach with a cross-sectional design. This research was conducted from January to November 2022. The total sample was 206 mothers with children aged 12-28 months in the Rawang Barat Health Center working area. The sampling technique used proportional random sampling. Data were collected through questionnaires and univariate, bivariate, and multivariate analyses were performed. The results of the study on the determinants of the infant’s basic immunization visits during the COVID-19 pandemic in the Rawang Barat Health Center working area, namely mother's knowledge (p-value<0.001), socioeconomic (p-value 0.444), family support (p-value<0.001), healthcare professionals support (p-value<0.001). The dominant factor related was the mother's knowledge (OR 24,301). The conclusion of this study that there was a significant correlation between maternal knowledge, family support, and health worker support but socioeconomic factors had no significant correlation with basic immunization visits for infants during the COVID-19 pandemic, and the most dominant factor related was the mother's knowledge